Pengaruh Love of Money dan Kecerdasan Sosial terhadap Sikap Mahasiswa Akuntansi di Universitas Bangka Belitung - Duwi Agustina; Suhaidar Suhaidar (Valid: Jurnal Ilmiah, 2020)
A good world of education will print students into prospective accountants who have a professional attitude based on moral and ethical standards. The analytical method used for testing the variables in this study uses PLS (Partial Least Square) using Smart PLS software.3. The sample collection technique used is the purposive sampling method. The sample used in this study was the 2017 accounting major students who were still active in lectures and had attended behavioral accounting courses with a total of 104 students. The first hypothesis in this study was accepted but love of money negatively affected the attitudes of students regarding the ethics of the accounting profession, this identified that students had a high love for money, the lower their attitudes about the ethics of the accounting profession, because when individuals are motivated by money then money will be the basis for doing something while the second hypothesis is accepted which means that social intelligence has a positive effect on student attitudes regarding the ethics of the accountant profession. as social creatures who need to understand each other